How Do Victims of Sexual Violence Benefit From Mutual Disclosure? An Exploratory Study of Women in South Korea - Choi, Eunsuhk (Journal of interpersonal violence, 2021)
Sexual violence victims in the Republic of Korea (henceforth, South Korea) have mutual support groups that provide a variety of programs promoting mutual disclosure between them. These programs are based upon the premise that responses within those groups are more supportive than conventional responses; however, there is no empirical evidence of mutual disclosure. The aim of the current study is to answer two research questions: (a) How do responses and outcomes of mutual disclosure compare with those of traditional disclosure? and (b) What themes describe mutual disclosure as distinguishable from a traditional one? A sample of 25 Korean sexual violence victims reported their disclosure experiences by responding to a survey and/or an in person interview. This study found that responses and outcomes of mutual disclosure were overall positive based on their similar victimized experience. The finding emphasizes a balance between a victim’s dual role as help-seeker and support provider for the benefits of mutual disclosure. Existing mutual support groups and relevant institutions should consider the aspects and effects of mutual disclosure to provide more opportunities for victims to speak out as well as to foster greater access to support.